Motivational interviewing : preparing people for change. - Miller, William Richard, 1947-; Rollnick, Stephen, 1952- (New York : Guilford, 2002)
This bestselling work has introduced hundreds of thousands of professionals and students to motivational interviewing (MI), a proven approach to helping people overcome ambivalence that gets in the way of change. William R. Miller and Stephen Rollnick explain current thinking on the process of behavior change, present the principles of MI, and provide detailed guidelines for putting it into practice. Case examples illustrate key points and demonstrate the benefits of MI in addictions treatment and other clinical contexts. The authors also discuss the process of learning MI. Chapters contributed by other leading experts address such special topics as MI and the stages-of-change model; applications in medical, public health, and criminal justice settings; and using the approach with groups, couples, and adolescents.
Keywords: Gesprekstechnieken -- Hulpverlening; Hulpverlening -- Methodiek; Motivatie